116k views
2 votes
Can someone help me thanks

Can someone help me thanks-example-1
User LastMove
by
5.8k points

2 Answers

6 votes
f(x)=-x^2-9x+20
f(9)=-(9)^2-9(9)+20
f(9)=-81-81+20
f(9)=-142
User Schaki
by
5.5k points
6 votes

Answer:

-142

Explanation:

So we have the function:


f(x)=-x^2-9x+20

To find f(9), substitute x for 9:


f(9)=-(9)^2-9(9)+20

Square the first term and multiply the second:


f(9)=-81-81+20

Add:


f(9)=-142

And that's our answer :)

User Nico Albers
by
5.4k points